Outstanding issues with Robert Russell's NIODA concerning quantum biology and theistic evolution - Qureshi-Hurst, E; Bennett, CT (Wiley, 2020)
Non‐Interventionist Objective Divine Action (NIODA), introduced by Robert John Russell, is a model of divine action drawing upon insights from quantum mechanics. It presents an intriguing and significant challenge to classical conceptions of divine action with far‐reaching consequences. When applying NIODA to theistic evolution, however, significant questions emerge that require attention. We identify and assess two sets of concerns. The first relates to quantum physics, particularly whether and how quantum occurrences influence mutations and evolution. We argue that the current empirical evidence is ambiguous in its support of the kinds of quantum action that Russell proposes, though emerging data from quantum biology look promising. The second set of concerns is metaphysical, especially concerning the problem of evil. NIODA gives Godextensive agency over evolution and genetics, which has adverse consequences for theodicy. We propose potential solutions to the problems highlighted in our article, both metaphysical and physical, to improve the viability of NIODA's application to theistic evolution.